Peri-Urban interface approaches to sustainable natural and human resource use - McGregor Duncan; Simon David; Thompson Donald (London Earthscan, 2006)
It covers the impacts of rapid urbanization on livelihoods, poverty and resources in the peri-urban zone, and lays out strategies for researching and overcoming these problems and promoting truly sustainable natural and human resource development.
Keywords: Environmental science; Natural resources; Sustainable development